KNOWLEDGE AND PRACTICES OF HAND WASHING FOR PRIMARY SCHOOL PUPILS AT MAJIRI WARD IN TANZANIA: A CROSS-SECTIONAL STUDY - Erasto Kinemelo; Paschal John Mbeho; Omari Saidi; Dativa George (Journal of Public Health Research and Community Health Development, 2026)
Background: Poor hand washing brings a major pathway through which fecal-oral diseases are transmitted. In low-and-middle-income countries, hand washing is still being practiced to a very low standard in particular during critical moments such as before eating and after using the toilet. The World Health Organization recommends hand washing as the best way to control diarrhea diseases among pupils. Purpose: This study aimed at assessing knowledge and practices on hand washing in primary school pupils at Majiri ward in Manyoni district council. Methods: A cross-sectional study design and multistage sampling technique from 4 primary schools were employed. 121 participants were involved in the study (117 pupils and 4 health teachers). Structured questionnaire, interview and observation methods were used in collecting data (questionnaires-pupils, interview-health teachers). SPSS software and Microsoft Excel were used for analyzing data. Results: 72% of pupils had adequate knowledge on hand washing because they knew water and soap as required to wash hands properly and 100% of pupils know that poor hand-washing cause diarrhea diseases. Hand washing practices were not done at about 98% and these pupils are more susceptible to diarrhea disease. It is because the water supply and other facilities for hand washing are limited (almost absent) at school premises. Conclusion: Hand washing practice among school pupils was too limited despite having adequate knowledge. For that focus, promoting and improving hand washing practices by implementing hand washing facilities in schools is mandatory to address the hand-washing practices gap among pupils at Majiri ward in rural areas.